Bagaimana Rayap dapat Digunakan sebagai Bioindikator - Teguh Pribadi (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
Ecosystem alterations not only affect habitat conditions but also have an impact on biotic components. The presence of organisms provides a response of habitat alteration can be used as indication organism. Indication organisms or bioindicator are key components in ecosystem management. This paper aims to evaluate and review the role of termites as bioindicator. Bioindicator defined as organisms or group of organism reflect and inform the ecosystem circumstance; environmental, ecological and biodiversity status as well as. Main criteria of bioindicator are as follow: taxonomical and biological characters of these organisms well-knew, cosmopolitan organisms, they have a well-response to habitat alteration, and their responses are closed correlated to all communities or properties of stress factors. Termites showed responses to environmental change, especially in habitat alteration. Termites responded to habitat alteration on termites composition change and termites richness decrease. Furthermore, termite’s richness strong correlated with another taxon in their community. Biological and taxonomical termites are well-known. In addition, a standard survey of termites has been developed to explore termite’s richness in tropics ecosystems. This implication, termites can be applied as one of the indicator organisms or bioindicator, notably their relation in ecological indicator and biodiversity indicator.